2023
DOI: 10.3390/ijms24054637
|View full text |Cite
|
Sign up to set email alerts
|

Phloroglucinol Inhibits Oxidative-Stress-Induced Cytotoxicity in C2C12 Murine Myoblasts through Nrf-2-Mediated Activation of HO-1

Abstract: Phloroglucinol is a class of polyphenolic compounds containing aromatic phenyl rings and is known to have various pharmacological activities. Recently, we reported that this compound isolated from Ecklonia cava, a brown alga belonging to the family Laminariaceae, has potent antioxidant activity in human dermal keratinocytes. In this study, we evaluated whether phloroglucinol could protect against hydrogen peroxide (H2O2)-induced oxidative damage in murine-derived C2C12 myoblasts. Our results revealed that phlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Many algal compounds exert their antioxidant effect by increasing the activity of endogenous antioxidant enzymes like SOD, CAT, and GPx [34], decreasing ROS production [35,36], and/or decreasing the expression of iNOS, leading to a decreased production of NO [37]. In skeletal myoblasts, algal compounds (phloroglucinol and Indole-6-carboxaldehyde) exerted antioxidant effects by regulating oxidative stress-induced apoptosis, mainly by decreasing mitochondrial dysfunction and modulating apoptosis-regulatory factors (e.g., caspases, Bcl-2, Bax, and cytochrome c) [38,39]. Some algal compounds (e.g., from Ecklonia cava and Sargassum thunbergii) were also able to decrease oxidative stress responses by modulating the signaling pathways, mainly by downregulating AMP-activated protein kinase (AMPK) and NF-κB, and upregulating Nrf2/ARE/HO-1/AKT pathways [38][39][40].…”
Section: Potential Health Benefits Of Algal Antioxidantsmentioning
confidence: 99%
“…Many algal compounds exert their antioxidant effect by increasing the activity of endogenous antioxidant enzymes like SOD, CAT, and GPx [34], decreasing ROS production [35,36], and/or decreasing the expression of iNOS, leading to a decreased production of NO [37]. In skeletal myoblasts, algal compounds (phloroglucinol and Indole-6-carboxaldehyde) exerted antioxidant effects by regulating oxidative stress-induced apoptosis, mainly by decreasing mitochondrial dysfunction and modulating apoptosis-regulatory factors (e.g., caspases, Bcl-2, Bax, and cytochrome c) [38,39]. Some algal compounds (e.g., from Ecklonia cava and Sargassum thunbergii) were also able to decrease oxidative stress responses by modulating the signaling pathways, mainly by downregulating AMP-activated protein kinase (AMPK) and NF-κB, and upregulating Nrf2/ARE/HO-1/AKT pathways [38][39][40].…”
Section: Potential Health Benefits Of Algal Antioxidantsmentioning
confidence: 99%
“…As previously mentioned, intracellular heme catabolism is mainly dependen activity of HOx, the enzymes catalyzing the rate-limiting reaction of heme degr HO exists in two isoforms: heme oxygenase 1 (HO-1) and heme oxygenase 2 Whilst HO-2 is constitutively expressed in all human tissues (although in d amounts), HO-1 is the inducible isoenzyme that can be found in a lower number o [16,17]. The expression of HO-1 is modulated by that of the nuclear factor eryt related factor 2 (Nrf2), activating the cell defense systems (including HO-1) a variety of stressors [18][19][20]. Pathological conditions causing oxidative/nitrosativ inflammation and mitochondrial malfunctioning are capable of activating the Nr axis as a cell/tissue protective response to increase the probability of cell/tissue to the stressor.…”
Section: Concentration Of Bilirubin In Ff Of Control Fertile and Pool...mentioning
confidence: 99%
“…Whilst HO-2 is constitutively expressed in all human tissues (although in different amounts), HO-1 is the inducible isoenzyme that can be found in a lower number of tissues [ 16 , 17 ]. The expression of HO-1 is modulated by that of the nuclear factor erythroid-2-related factor 2 (Nrf2), activating the cell defense systems (including HO-1) against a variety of stressors [ 18 , 19 , 20 ]. Pathological conditions causing oxidative/nitrosative stress, inflammation and mitochondrial malfunctioning are capable of activating the Nrf2/HO-1 axis as a cell/tissue protective response to increase the probability of cell/tissue to survive the stressor.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al have demonstrated that the polyphenol Phloroglucinol showed strong antioxidant activity, protecting C2C12 muscle cells from H 2 O 2 -induced oxidative stress. Like other polyphenols, this molecule has been shown to enhance Nrf2/HO-1 signaling activity, thus activating the antioxidant enzymatic cellular system [ 8 ]. This cell defense mechanism is particularly important because it allows cells to adapt and better defend themselves against oxidative stress.…”
mentioning
confidence: 99%